Delays in attentional processing when viewing sexual imagery: the development and comparison of two measures - Gress, Carmen L.Z. (Legal and criminological psychology, 2013)
Purpose. Critically important to effectively treating and managing sexual offending is the identification or validation of an offender's deviant sexual interests as the nature of their sexual interests is what demarcates repetitive sexual offenders from non-offenders and lower risk offenders. As an alternative or verification to self-report or phallometric measures, focus has turned to attention-based measures. These measures assess sexual content-induced delay (SCID), a specific form of attentional bias associated with preferred sexual content (images or text). Viewing time (VT) and choice reaction time (CRT) were developed and utilized to assess sexual interest via SCID (Geer & Bellard, 1996) and examine the measures’ clinical utility via estimates of sensitivity and specificity. Method. Participants were 44 youth non-sexual offenders, 60 university students, and 22 adult sexual offenders. Differences between groups were examined on various sub-scores and receiver operator characteristic curves provided information on clinical utility. Results. The VT and CRT measures produced subtest scores with high reliability in all three samples. There were significant differences in VT between the adult sexual offenders and the youth non-sexual offenders, but not between the youth non-sexual offenders and the university students. Some of the VT subtests demonstrated good clinical utility in their ability to differentiate adult heterosexual sexual offenders from non-sexual offenders (e.g., area under the curve (AUC) = 0.87 female mature images, 0.88 male child images). Interestingly, the VT and CRT measures provided significantly different results. Conclusion. The results of this study provide further evidence that measures of SCID are accurate and are useful as indications of sexual interest. Differences between measures suggest, however, that further work is required.